(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In the Message of the Head of State Kassym-Jomart Tokayev on March 16, 2022 to the people of Kazakhstan “New Kazakhstan: the path of renewal and modernization”, it was announced that the country faces ambitious goals that will actually become the basis for building a New Kazakhstan. The President emphasized that the management system focused on over-concentration of powers has already lost its effectiveness. It is not capable of consolidating civil society with its diversity of views and beliefs. Therefore, the President noted, we need verified steps to restructure the political model of Kazakhstan’s development.” The article deals with the problems of formation and development of a true system of local self-government in Kazakhstan, since, as the President of the Republic of Kazakhstan K.Zh. Tokayev noted, it is necessary to “implement a real decentralization of local self-government”. The Constitution of the Republic of Kazakhstan prescribes norms regulating the activities of local self-government bodies, but in practice these constitutional norms have not been implemented. The Head of State noted that “there was an imitation, not local self-government.” President of the Republic of Kazakhstan Tokayev K.Zh. emphasized that “today local self-government bodies have a hybrid nature, being at the same time an institution of local public administration and local self-government. Therefore, it is necessary to clearly define the powers of both maslikhats and akimats on a legislative basis. It is necessary to clearly define their functions and powers and provide them with everything necessary - material and technical base and sufficient financial resources.